The Expression of Innate Immunity Responsible Genes in Human Macrophages Encountering Mycobacterium Tuberculosis - Farhang Babamahmoodi; Hadiseh Saberi; Farzaneh Rabiae; Hossein Jalali; Mohammad Reza Mahdavi (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Macrophages are the primary cells that encounter this pathogen, and Mycobacterium tuberculosis (MT) has developed several strategies to survive within the macrophage cytoplasm. One of the primary cellular targets of Mycobacterium species are macrophages. These bacteria employ various strategies to survive and proliferate within phagosomes, including inhibiting phagosome acidification and preventing phagosome-lysosome fusion. On the other hand, the significance of macrophage polarization and plasticity in response to infectious agents is well-established, particularly in distinguishing between M1 and M2 macrophages. The DUSP14 gene regulates the Mitogen-Activated Protein Kinase (MAPK) pathway, while RAP2A is a member of the GTPase family. Considering the roles of the DUSP14 and RAP2A genes in innate immunity, the aim of this study is to investigate the expression of these genes in macrophages from healthy individuals infected with PB8, H37Rv, and MTBRils strains. This analysis seeks to provide a more comprehensive understanding of the mechanisms underlying innate immune function. Materials and methods: Peripheral blood mononuclear cells (PBMCs) were isolated from 40 cc of peripheral blood drawn from five healthy individuals with negative PPD test results, using Ficoll density gradient centrifugation. The extracted cells were counted using a cell counter and cultured in StemSpan medium supplemented with 2 ml of lipid cholesterol and 5 ml of Pen/Strep (10x) per 500 ml of culture medium. After nine days, the cells were infected with two MT strains: H37Rv, MTBRils, and PB8. Total RNA was extracted from the infected cells 8, 18, and 48 hours post-infection. cDNA synthesis was performed, and real-time PCR was conducted using Takara master mix to analyze RAP2A and DUSP14 gene expression. The relative fold changes in gene expression were calculated using the 2–∆∆Ct method, with statistical analyses performed using GraphPad Prism version 8 and SPSS version 20. Results: The results showed that 4 hours after infection with the H37Rv strain, the expression of the RAP2A gene was higher than in groups infected with the other two strains, although the differences were not statistically significant. Additionally, while DUSP14 expression was not significantly increased 4 hours after infection with any of the three strains, its expression was higher in cultures infected with the PB8 strain. After 48 hours of MT infection, RAP2A gene expression decreased in macrophages infected with the H37Rv and MTBRils strains compared to the control and PB8-infected cells. Similarly, DUSP14 gene expression was significantly decreased in cells infected with the H37Rv and MTBRils strains compared to PB8-infected cells and controls. Conclusion: The observed decrease in RAP2A gene expression in macrophages infected with the H37Rv and MTBRils strains is associated with reduced GTPase activity, suggesting that these strains may disrupt phagosome function, potentially shifting responses towards M2 macrophage polarization. Further studies investigating the role of RAP2A and DUSP14 gene polymorphisms in MT survival are recommended.